Flipping the College Classroom An Evidence-Based Guide - Roehling, Patricia V. (Springer International Publishing, 2018)
Flipped learning-in which students view recorded lectures outside of the classroom and then utilize class time to develop a broad range of knowledge and skills-is a relatively new phenomenon. This timely volume examines and organizes the emerging research on flipped learning in higher education. It identifies the types of courses, material, and learning objectives that are most effectively flipped, with specialized advice for faculty in STEM fields, the social sciences, and humanities. The book also provides evidence-based guidance on how to create and disseminate engaging recorded lectures; develop and implement in-class exercises and projects that help students meet learning objectives; orient students to the flipped classroom; and assess the effectiveness of flipped learning. .